Analysis of Grammatical Errors in Writing Chinese Sentences by Students of the School of Liberal Arts, University of Phayao - Sasithorn Nuritamon (Journal of Humanities and Social Sciences Mahasarakham University, 2022)
The purpose of this research is to analyze grammatical errors in Chinese sentence writing of the students of School of Liberal Arts, University of Phayao. The sample group included all the 121 students enrolled in the course 142232 ‘Development of Chinese Reading and Writing Skills2’, Chinese Language Program Academic year 2020/2. Analyzing the data used the method of error rate. Four types of errors were categorized as follows: 1) Errors in ordering a sentence 2) Errors in using near synonym words 3) Errors in writing omissions 4) Errors in adding words or components 5) Errors in mingling 6) Other errors. The results showed that error in mingling is the most common mistake. In addition, the researcher also found another 3 kinds of errors as follows: 1) Error in words’ part of speech usage 2) Error in sentence construction 3) Error in Chinese character writing.